Status of Retail Meat Units In Hisar City - Beniwal, B.S.; om, Hari; malik, Renuka; Prakash, Chetan (Journal of Meat Science, 2014)
A survey of Hisar city revealed that there were 43 raw meat shops/outlets and 72% of these shops were set up during the preceding 10 years. The area of the shop/ outlet ranged between 64-325 square feet with an average of 123 square feet. All these shops had cemented/ pucca floor. 84% of the shopkeepers/butchers were either illiterate or primary pass only. Animals/birds were slaughtered and sold in the same shop in 98% of the cases and the total sale of meat per day was 1363.5, 307.5, 150.0 and 25.0 kg for poultry, goat, pig and fish, respectively. Out of offals only goatskin, skull and hooves were sold; other offals were thrown away. Only 7% of the shops had a wire gauge door and the average personal hygiene was Moderately Good to Good while the equipments and shop hygiene was Neither Good nor Bad to Moderately Good. The total average investment on an outlet (excluding land) was equal to 550.0 % and monthly rent was 21.64 % of sale proceeds of one day. 16% of shopkeepers had ownership of the shop and 84% were tenants. 86% of the shops were registering increase in their business.